Serial cytokine alterations and abnormal neuroimaging in newborn infants with encephalopathy. (16th February 2017) - O'Hare, Fiona M.; Watson, R William G.; O'Neill, Amanda; Segurado, Ricardo; Sweetman, Deirdre; Downey, Paul; Mooney, Eoghan; Murphy, John; Donoghue, Veronica; Molloy, Eleanor J.
Abstract: Aim: Inflammatory cytokines may play a role in the final common pathway in the pathogenesis of hypoxic‐ischaemic injury in experimental models. We aimed to profile the systemic pro‐and anti‐inflammatory response over the first week of life in term infants at risk of neonatal encephalopathy. Method: In a tertiary referral university neonatal intensive care unit, serial blood samples were analysed from 41 term infants (requiring resuscitation at birth) in this prospective observational pilot study. Serum levels of 10 pro‐and anti‐inflammatory cytokines were evaluated including interleukin(IL)‐1 α, IL‐1 β, IL‐6, IL‐8, IL‐10, tumour necrosis factor(TNF)‐ α, interferon (IFN)‐γ, vascular endothelial growth factor (VEGF), granulocyte/colony‐stimulating factor (G‐CSF) and granulocyte macrophage/colony‐stimulating factor (GM‐CSF). Results: Infants with neonatal encephalopathy and abnormal neuroimaging (n = 15) had significantly elevated granulocyte macrophage/colony‐stimulating factor at 0‐24 h and interleukin‐8, interleukin‐6 and interleukin‐10 at 24–48 hour. Tumour necrosis factor‐ α and vascular endothelial growth factor levels were lower at 72–96 hour (p < 0.05). Significantly elevated levels of interleukin‐10 were associated with mortality. Conclusion: Serum cytokine changes and innate immune dysregulation in the first week of life may be indicators of outcome in neonatal encephalopathy but require validation in larger studies.